The modulation of emotional and social behaviors by oxytocin signaling in limbic network - Triana-Del Rio, Rodrigo; Ranade, Sayali; Guardado, Jahel; LeDoux, Joseph; Klann, Eric; Shrestha, Prerana (Frontiers in Molecular Neuroscience, 2022)
Neuropeptides can exert volume modulation in neuronal networks, which account for a well-calibrated and fine-tuned regulation that depends on the sensory and behavioral contexts. For example, oxytocin (OT) and the oxytocin receptor (OTR) trigger a signaling pattern from intracellular cascades, synaptic plasticity, and network regulation, increasing the signal-to-noise ratio for sensory-dependent threat and social responses. Oxytocin receptors are mainly expressed by GABAergic neurons, inputting such volume inhibition in specific pathways. Activation of OTRs in emotional circuits is necessary to acquire stress/threat response choices. When emotional memories are retrieved, OTR-expressing cells appear to be gatekeepers of the threat response choice/discrimination. OT signaling has been implicated in social memory and approach in social circuits. The interaction between OT and OT receptors is the basis for various social and emotional behaviors. Thus, in this review, we describe the cellular and molecular mechanisms that underlie the neuromodulation by oxytocin and how those intracellular signaling cascades could be potential pharmacological targets for neuropsychiatric disorders, supported by studies in animal models and clinical populations. The variation in the intracellular signaling may account for the wide variety of downstream effects oxytocin exerts. Thus, understanding the intracellular signaling, synaptic plasticity pathways, and secondary messengers will help design intervention therapies.